An Analysis of Moral Values through Some Characters in the Novel Lampuki by Arafat Nur - Rahmi, Nailur (Journal of English Education and Social Science, 2023)
This thesis is a research on the moral values that exist in several characters and events in the novel Lampuki. This novel is one of Arafat Nur's best works. This novel is concerned with the Aceh conflict and describes in detail about war, social behavior, characters, society, and human values. Many moral messages can be learned, as well as adding insight into the appearance of Aceh's struggle at that time. Therefore, the scope of this research is focused on "An Analysis of Moral Values Through Some Characters". The problem in this research is (1) How is the description of Acehnese people's relations regarding moral values in the novel? (2) What are the moral values of some characters in the novel? The methods used in this research are (1) library research, (2) and the techniques used are: reading the novel many times, taking the information related to the topic, specifying the data following the information. The results of this research concerned moral values in the several characters in the novel are; (1). The morality of divinity: worship, understanding religion, loving teachers, and some bad morals, namely, not covering the private parts, and adulterous; (2) Ideological morality and philosophical morality: care about unity and integrity; (3) The morality of ethics and decency: patience, caring for others, friendly, mercyful, humility, and protective. And there are bad morals, namely, fierce, arrogant, and opinionated; (4) The morality of discipline and legal morality: refusing to become a marijuana farmer, refusing to consume marijuana, and bad morals are selling marijuana. Keywords : Novel Lampuki, moral values, characters